Hubungan Kecerdasan Spiritual Quetion dan Emosional Quoetion dengan Prestasi Belajar pada Mahasiswa Keperawatan Angkatan 2020 - Maulana, Nova (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to determine the relationship between Islamic spiritual intelligence and emotional intelligence with learning achievement in nursing science students class 2018 Academic Year 2020/2021. The method used in this research is quantitative methods. The population in this study were all students of the nursing study program batch 2018 STIKes Surya Global Yogyakarta, the total population was 148. The sampling technique in this study used purposive sampling with a sample size of 60 respondents. Data were analyzed using Kendall tau statistical test and multivariate analysis using multiple linear regression. Based on the results of the Kendall Tau test, the value of r count is (Islamic spiritual intelligence) 0.399, (emotional intelligence) 0.587. And for multivariate results of 17,825 with asymp numbers. Sig. in each measurement (emotional intelligence is 0.000 (p <0.05) while (Islamic spiritual intelligence) is 0.082 (p> 0.05), so that Ho is rejected and Ha is accepted.Thus there is a relationship between Islamic spiritual intelligence and emotional intelligence with learning achievement at semester V student of the STIKes Surya Global Yogyakarta Nursing Program. There is a relationship between Islamic spiritual intelligence and emotional intelligence with learning achievement in the fifth semester students of the STIKes Surya Global Yogyakarta Nursing Program.